A Biochemical View on Intermittent Fasting’s Effects on Human Physiology—Not Always a Beneficial Strategy - Zambuzzi, Willian Fernando [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; Wang, Zifan; Peppelenbosch, Maikel P. (MDPI, 2025)
Intermittent fasting (IF) has emerged as a widely practiced dietary regimen, increasingly utilized in both clinical and non-clinical settings for its potential health benefits. Evidence suggests that IF can improve metabolic health by enhancing insulin sensitivity, reducing inflammation, and aiding weight management. Recent studies have also explored its role in mitigating obesity-related diseases, such as type 2 diabetes and non-alcoholic fatty liver disease, and its ability to support cardiovascular health and mental function. The effects of IF, however, vary depending on individual health conditions. Some patients show no clinical improvement, while others experience worsened outcomes. Mechanistically, IF induces metabolic switching and activates adenosine monophosphate-activated protein kinase (AMPK), both of which contribute to its therapeutic potential. These responses are influenced by factors such as underlying pathology, baseline metabolic state, and dietary composition. While preclinical data indicate potential therapeutic effects in diseases like cancer, rheumatoid arthritis, and neurodegenerative conditions, these findings are not yet sufficiently supported by human studies. This review argues that IF holds promise as a disease-modifying intervention. However, its implementation should be personalized according to patient-specific characteristics, and future clinical trials must prioritize identifying optimal fasting protocols to maximize therapeutic outcomes.